2012
DOI: 10.3233/jad-2012-120718
|View full text |Cite
|
Sign up to set email alerts
|

Dendritic Spine Abnormalities in Hippocampal CA1 Pyramidal Neurons Underlying Memory Deficits in the SAMP8 Mouse Model of Alzheimer's Disease

Abstract: Abstract. SAMP8 is a strain of mice with accelerated senescence. These mice have recently been the focus of attention as they show several alterations that have also been described in Alzheimer's disease (AD) patients. The number of dendritic spines, spine plasticity, and morphology are basic to memory formation. In AD, the density of dendritic spines is severely decreased. We studied memory alterations using the object recognition test. We measured levels of synaptophysin as a marker of neurotransmission and … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

6
25
0

Year Published

2012
2012
2020
2020

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 48 publications
(31 citation statements)
references
References 41 publications
(50 reference statements)
6
25
0
Order By: Relevance
“…Furthermore, several studies have characterized alterations in the dendritic spine density in mouse models of AD, including a significant decrease in dendritic spine density in the hippocampus of the J20 and APP/PS1 mice [83] and in the CA1 subzone in Tg2576 and APP/Lo mice [84]. Dendritic spine state alterations have been described in SAMP8 [70].…”
Section: Histopathological Similarities In Samp8 and Admentioning
confidence: 99%
See 2 more Smart Citations
“…Furthermore, several studies have characterized alterations in the dendritic spine density in mouse models of AD, including a significant decrease in dendritic spine density in the hippocampus of the J20 and APP/PS1 mice [83] and in the CA1 subzone in Tg2576 and APP/Lo mice [84]. Dendritic spine state alterations have been described in SAMP8 [70].…”
Section: Histopathological Similarities In Samp8 and Admentioning
confidence: 99%
“…Del Valle et al [70] demonstrated altered synaptic dendrite distribution and number in SAMP8 compared with SAMR1. This suggests that the learning capabilities of SAMP8 decrease, since thin spines have been related with information acquisition (learning) [108][109][110].…”
Section: Behavioral Characteristicsmentioning
confidence: 99%
See 1 more Smart Citation
“…Synapses loss, especially dendritic spines loss which manifests as morphological changes is closely correlated with cognitive impairment [59]. The decrease of synaptic efficacy in the hippocampus is much earlier than the appearance of neuron degeneration [60]. Previous work has reported that the loss of synapses in the dendritic spines and dendrites was the main reason for the decrease of the synapse in APP/PS1 Tg mice [61].…”
Section: Synaptic Plasticitymentioning
confidence: 99%
“…In an experimental study on mice with accelerated senescence, the use of Golgi staining revealed that the dendritic spines started to decrease as the age of the animals advanced and their memory declined [16].…”
Section: Editorialmentioning
confidence: 99%